Well when you simplify it you get this,
0=-24,
Do what’s inside the parentheses first
3-3 is 0, 3•0 is 0
2•positive 3 is 6
6- -30 is -24
So you have 0=-24
Or just -24 :)
Answer:
1109
Step-by-step explanation:
you can subtract the terms to see the difference between them
-11-(-27)=16
The sequence is increasing by 16
you can plug that 16 in the formula for d
a_n=a_1+(n-1)d
a_n=a_1+(n-1)16
n represents the term you want to find in this case the 72nd
a sub 1 is the first term of the sequence in this case -27
a_72=-27+(72-1)16
a_72=-27+(71)16
a_72=-27+1136
a_72=1109
The answer is <span><span>−<span>6<span>x2</span></span></span>+<span>7x</span></span>−<span>212</span>